2023
DOI: 10.1111/cas.15851
|View full text |Cite
|
Sign up to set email alerts
|

PLOD2 promotes colorectal cancer progression by stabilizing USP15 to activate the AKT/mTOR signaling pathway

Abstract: Colorectal carcinoma (CRC) is one of the most common malignant tumors in the world; it is the third most diagnosed cancer in males (10.6%) and females (9.4%). 1,2 CRC is also the third leading cause of cancer death in both males (9.3%) and females (9.5%). 1 Lifestyle factors, such as obesity, smoking, and alcohol, are significant and can be addressed through therapeutic interventions. 3 Pre-cancer screenings like colonoscopies have also been improved. 3,4 However, the incidence and death rates of CRC remain hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Both in vivo and in vitro studies have demonstrated that PLOD2 knockdown inhibits the proliferation, invasion, and anchorage-independent growth of GBM ( 108 , 110 , 111 ). Minoxidil, a confirmed PLOD2 inhibitor ( 112 ), could suppress tumor metastasis, in part, by reversing collagen cross-linking in ECM ( 113 , 114 ). Moreover, studies have found that minoxidil cloud increases the antitumor drug permeability of the blood-brain tumor barrier, resulting in improved and selective delivery to brain tumors, including GBM ( 115 , 116 ).…”
Section: Antifibrosis Therapies Explored and Tested In Gliomamentioning
confidence: 99%
“…Both in vivo and in vitro studies have demonstrated that PLOD2 knockdown inhibits the proliferation, invasion, and anchorage-independent growth of GBM ( 108 , 110 , 111 ). Minoxidil, a confirmed PLOD2 inhibitor ( 112 ), could suppress tumor metastasis, in part, by reversing collagen cross-linking in ECM ( 113 , 114 ). Moreover, studies have found that minoxidil cloud increases the antitumor drug permeability of the blood-brain tumor barrier, resulting in improved and selective delivery to brain tumors, including GBM ( 115 , 116 ).…”
Section: Antifibrosis Therapies Explored and Tested In Gliomamentioning
confidence: 99%
“…Further, the acetylation level of eEF1A1 K439 was higher in CRC patients than in healthy individuals [119]. Procollagen-lysine, 2-oxoglutarate 5-dioxygenase 2 (PLOD2) serves as a lysyl hydroxylase, which has been found to interact with USP15, which promotes CRC invasion and metastasis via activating the AKT/mTOR pathway [120] (Figure 6).…”
Section: Non-classical Ptms and Crc Metastasismentioning
confidence: 99%